Persepsi Pengguna Terhadap Perkhidmatan Pengangkutan Awam : Kajian Kes Laluan Medan - Pematang Siantar [HE151. D521 2007 f rb]. - Juli Isnaini, Dewi Budhiartini (2007)
This research was initiated by the process of studying, understanding, identifying and analyzing the transportation problems based on the phenomena which affect the consumer’s perception on the public transportation service, Medan – Pematang Siantar route.